Manajemen Peningkatan Mutu Madrasah Dalam Membentuk Madrasah Efektif di Era Global - Antiq Kusthon Tiniyyah; Danu Sugiarto; Prim Masrokan Mutohar; As’aril Muhajir Muhajir (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2023)
In the 21st century information and communication era, schools now face much bigger challenges than in the past. Schools that are able to adapt to this era are certainly not just any schools; rather it is a truly effective school capable of producing graduates who are ready for the changes that the future will bring. The research method used in this research is literature review or literature review. The data collection method for this study was taken from data sources, the data sources used in this study were obtained from journals and books. The journals used as reference sources are journals with the theme Quality Management and Effective Schools, 16 journals and books analyzed, spanning 2014-2022. The results of this study are that effective schools through quality management must pay attention to the school context, namely the learning process and its achievements. In conclusion, in the school context, the experience-based learning process (andragogy) is a characteristic that is often used by school principals and teachers based on experience for and in order to explore new experiences for their students. Quality schools are often oriented as good schools or effective schools, the two are interrelated. Good quality management supports the realization of an Effective School